Building and Maintaining a Data Warehouse - Silvers, Fon (CRC Press, 2009)
As it is with building a house, most of the work necessary to build a data warehouse is neither visible nor obvious when looking at the completed product. While it may be easy to plan for a data warehouse that incorporates all the right concepts, taking the steps needed to create a warehouse that is as functional and user-friendly as it is theoretically sound, is not especially easy. That’s the challenge that Building and Maintaininga Data Warehouse answers.